2019
DOI: 10.1002/bab.1851
|View full text |Cite
|
Sign up to set email alerts
|

Liposoluble compounds from Ganoderma lipsiense grown on solid red rice medium with antiparasitic and antibacterial properties

Abstract: Liposoluble molecules are a group of compounds that display potent biological and therapeutic properties. The present study aimed to identify liposoluble molecules produced by Ganoderma lipsiense grown in red rice medium using solid‐state fermentation (SSF) techniques, and to investigate the antigiardial and antibacterial activities potential of extracts in vitro. Eighteen fatty acids and derivatives were identified by gas chromatograph‐mass spectrometry (GC‐MS) analysis in G. lipsense extract. Qualitative (Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Nonanoic acid has been found in Laetiporus sulphureus mushroom as antimicrobial against Micrococcus flavus and P. aeruginosa (Petrović et al, 2013). Bactericidal 2-dodecen-1-yl(-) succinic anhydride has been identified in Agaricus bisporus mushroom and endophytic fungi Fusarium fujikuroi and Aspergillus tubingensis (Nisa et al, 2020;Mohamed, 2012) while linoleic acid ethyl ester has also been reported in Ganoderma lipsiense mushroom grown on red rice as effective antimicrobial agents against Pseudomonas aeruginosa and Staphylococcus aureus (Costa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonanoic acid has been found in Laetiporus sulphureus mushroom as antimicrobial against Micrococcus flavus and P. aeruginosa (Petrović et al, 2013). Bactericidal 2-dodecen-1-yl(-) succinic anhydride has been identified in Agaricus bisporus mushroom and endophytic fungi Fusarium fujikuroi and Aspergillus tubingensis (Nisa et al, 2020;Mohamed, 2012) while linoleic acid ethyl ester has also been reported in Ganoderma lipsiense mushroom grown on red rice as effective antimicrobial agents against Pseudomonas aeruginosa and Staphylococcus aureus (Costa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Solid-state cultivation or solid-state fermentation (SSF) is a technique that involves the growth of microorganisms on moist solid substrates in the absence of free-flowing water (Wang et al, 2012). SSF is suitable for the daily formation of a number of compounds because it mimics the natural habitat of filamentous fungi (Costa et al, 2020). A well-known example is the application of SSF in production of "Anka" from Monascusfermented rice with antihypertensive, antioxidant, antimicrobial, and anticancer properties (Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Extracts and fractions of Ganoderma have mainly poor or lack of activity. Regardless of the Ganoderma species, the MIC values for extracts most often range from 500 μg/ml to even 512 mg/ml (Sa-Ard et al, 2015;El Zawawy and Ali, 2016;Ergun, 2017;Costa et al, 2020;Savin et al, 2020;Serrano-Márquez et al, 2021). For single strains, incl.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…As mentioned above, many ergostane steroids are found in both mushrooms and plants. In particular, this applies to triol 73 found in various fungal species [ 101 , 103 , 105 , 235 ]. Among sixty-three compounds isolated from bamboo Sinocalamus affinis and studied as inhibitors of estrogen biosynthesis, triol 73 showed the highest activity with an IC 50 value of 0.5 μM [ 241 ].…”
Section: Polyolsmentioning
confidence: 99%